Pengembangan Video Pembelajaran Bahasa Arab Berbantuan Aplikasi Kinemaster - Nisa, Khoirun (UIN Sunan Gunung Djati Bandung, 2023)
This research is motivated by the importance of using digital media as online learning media in the Industry 4.0 era. This study aims to describe the video development process using the kinemaster application as Arabic learning media to increase creativity and innovation for educators in developing online learning media. The Kinemaster application is software on a smartphone that can be a solution in developing today's online learning media. This research uses the research and development method (Research and development) using the ADDIE instructional model; the development model has five stages, namely (a) analysis, (b) design, (c) development, (d) implementation, and (e) evaluation. However, this research is still in the ADD stage: analysis, design, and development. This research describes video editing using the kinemaster application as an online learning medium. The results of the limited trial research on 20 Class VI elementary school students, with a percentage of 85%, were excellent. The final results show that 1) kinemaster applications in Islamic Religious Education subjects is feasible to use in the online learning process; 2) creative and innovative video viewing can increase learning understanding for students.